Damping Factors in the Interpretation of Geoelectric Data (Case Study: Malalak Agam Rock Structure) - Sembiring, Ayu Ashari; Akmam, Akmam (ALSYSTECH Journal of Education Technology, 2024)
This research aims to optimize the damping factor so that the results of Geoelectric data inversion are stable and in accordance with current geological conditions in Malalak Agam. This type of research is a descriptive research using secondary data in the form of pseudo-type resistance data and electrode spacing obtained from research in the field of Geoelectric exploration in the Department of Physics at Padang State University (UNP). This data is obtained from Geoelectric secondary data and location supporting data. The geoelectric data processing stage is carried out using Res2dinv software which is used to model in 2-D using least-square inversion. The results showed that based on the interpretation of the data, the suitable damping factors in Malalak Agam District, West Sumatra, were the initial damping factor (0.2 – 0.25) and the minimum damping factor (0.01 – 0.1) because on trajectory 2 At the third measurement point 160 meters from point 0 was dominated by limestone and sandstone rocks. The existence of Limestone acts as a slip field, and there is Sandstone right above it which causes large-scale landslides from the first to fifth measurement points (315-160 meters from point 0) and on trajectory 3 at this time there is a landslide with a small volume, it is estimated that the avalanche is at the second measurement point 120 meters from point 0 with an avalanche thickness ranging from approximately 5 meters.